Winter of 1974-75, Red Rock area and Pleasantville, Iowa field notes, and Snowy Owl reports - Black, Gladyset al (1974)
Winter of 1974-75, Red Rock area and Pleasantville, Iowa field notes were submitted by Gladys Black along with a cover letter to Vernon M. Kleen dated March 19, 1975, a newspaper article and a map. The article was one she wrote for the Des Moines Register called "Reports two Snowy Owls seen in central Iowa," and the map showed the number of Snowy Owl observations in Iowa counties, November 1974-March 1975. The letter summarized the findings on Snowy Owls from responses to the newspaper article, and the impact of a blizzard January 10-11 in northwest Iowa that killed many birds and livestock. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1974-1975. Epson - sheet feed/flatbed